1998
DOI: 10.13181/mji.v7i4.750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc supplementation in children under three years of age with acute diarrhea in Indonesia

Abstract: Diarrheal diseases continue to be an important cause of childhood mortality in Indonesia. Dianhea leads to excess zinc losses and could contribute to zinc deficiency. Zinc deficiency in particular is known to limit regeneration of gut epithelium and consequently to delny recovery from diarrhea. To evaluate the effect of zinc supplementation in children on the duration of diarrhea we conducted a randomized, double blind, controlled tial.The treatment group received syrup incorporatinç zinc acetate providing 4-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
1
24
1
Order By: Relevance
“…In present study, it has been shown that serum alkaline phosphatase was low in all patients, may be correlating with zinc deficiency, but we were not able to do the follow up study on the seventh and fourteenth day supplementation. This is the limitation of our study that rise in serum alkaline phosphatase with serial zinc supplementation was not followed as supported by other studies [15]. But as we have measured serum zinc on third day of supplementation with zinc syrup, it was seen that serum zinc has shown significant rise on third day, that suggests that sufficient absorption and replenishment of body zinc occurred with the double dose of zinc used.…”
Section: Discussionmentioning
confidence: 70%
“…In present study, it has been shown that serum alkaline phosphatase was low in all patients, may be correlating with zinc deficiency, but we were not able to do the follow up study on the seventh and fourteenth day supplementation. This is the limitation of our study that rise in serum alkaline phosphatase with serial zinc supplementation was not followed as supported by other studies [15]. But as we have measured serum zinc on third day of supplementation with zinc syrup, it was seen that serum zinc has shown significant rise on third day, that suggests that sufficient absorption and replenishment of body zinc occurred with the double dose of zinc used.…”
Section: Discussionmentioning
confidence: 70%
“…Zinc supplementation has been associated with clinical reduction in duration and severity of diarrhea in infants and young children [5][6][7]. It also reduced the risk of continued diarrhea, measured as decreased frequency of prolonged diarrhea and the number of days with watery stools.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of oral rehydration solution has been successful and substantial global progress has been made in reducing mortality due to diarrhea, current rates of morbidity as a result of infectious diarrhea remain a major public health problem [4]. Studies on zinc supplementation in children with acute diarrhea have been shown to be effective in reducing the duration of diarrhea and preventing persistent diarrhea [5][6][7]. Results of pooled analyses showed that children taking zinc supplements had a 15% lower probability of continued symptoms on a given day during an episode of acute diarrhea [6].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Thus, therapeutic use of zinc has the potential of reducing the annual 2.5 million childhood diarrheal deaths. [1][2][3][4][5][6][7] Thus, therapeutic use of zinc has the potential of reducing the annual 2.5 million childhood diarrheal deaths.…”
mentioning
confidence: 99%
“…We chose a relatively large dose because zinc is lost in the stool during diarrhea, 15 and because of the variable effect of zinc in previous studies. [1][2][3][4][5][6][7] The supplement was given daily by field workers or by caretakers to assess efficacy and effectiveness, respectively, of zinc on the duration of acute childhood diarrhea, on the proportion of episodes that became prolonged, and on stool frequency. We also monitored the children for adverse effects.…”
mentioning
confidence: 99%